Rancang Bangun Pompa Hidram Untuk Kebutuhan Air Pada Daratan Tinggi Dengan Memanfaatkan Arus Aliran Air Sungai - Suherman, Andi; Hasanudin, La; Aksar, Prinob (Enthalpy : Jurnal Ilmiah Mahasiswa Teknik Mesin, 2022)
In rural areas, water supply is needed for agricultural, livestock, and fishery activities. In this problem a pump with the right technology, efficiency, and economy is needed so that its management does not depend on fuel and electricity. As a solution to this problem is the use of a hydraulic ram pump. Hydram pumps are an alternative in distributing water from low places to high places. This study aims to design a hydraulic ram pump at Cemping Ground. In this study, the main system is a hydraulic ram pump (hdyram pump) which can drain water from a low place to a high place without using electricity. The flow capacity produced by this pump at a height of 5 meters is 0,000057 (m3/s) or 0,057 (liter/s), the flow rate produced by this tool is 0,00072 (m/s), the efficiency of the hydraulic ram pump produced is 75,83 %, it takes 58,26 minutes per day to meet the 200 L water requirement, for the stress that occurs in the pipe is 0,0554 N/mm2 and for the strain that occurs in the pipe is 0,0000185.Keywords: Alternative, Tool, Design, Pump, Hydraulic